E-264 Novel use of the comaneci device to enhance flow diverter wall apposition: experience with 26 consecutive cases. (23rd July 2022) - Campos, J; Zarrin, D; Meyer, B; Golshani, K; Beaty, N; Bender, M; Colby, G; Coon, A; Lin, L
Abstract : Background: The Comaneci device (Rapid Medical, Yokneam, Israel) is an FDA approved (2019) retrievable stent device to assist in coil embolization. The use of the Comaneci device allows for the benefits of balloon-remodeling coil embolization without limiting antegrade blood flow. Here we describe a unique application of the Comaneci device to improve flow diversion stent wall opposition. Methods: We retrospectively reviewed a prospectively maintained IRB-approved institutional database of aneurysms treated with flow diversion (FD) to identify cases where a Comaneci device was utilized. We evaluated patient demographics, aneurysm type, procedural details including embolization device used, and periprocedural events and complications. Technical success was defined as successful FD implantation and adjunctive use of the Comaneci device without additional balloon angioplasty. Results: Surpass FD embolization with adjunctive Comaneci angioplasty was performed in 26 aneurysm cases over a 12-month period (December 2020 to 2021). Mean patient age was 70 +/- 9 years. Dual antiplatelet regimen consisted of aspirin 81 mg and either clopidogrel 75 mg or ticagrelor (60 or 90 mg BID) daily dosing, with an average pre-operative P2Y12 PRU of 27 +/- 39. Eighty-five percent (n=22) were located in the anterior circulation. Aneurysms treated included 13 (45%) internal carotid artery, 3 (10%) middle cerebral artery, 6 (21%) anterior cerebral artery, 1 (3%) vertebral artery, 3 (10%) basilar artery aneurysms. FD implantation was successful in all (100%) cases. The technique of Comaneci device deployment and retrieval was successfully carried out in all (100%) cases without the need for traditional balloon angioplasty. Conclusion: This series demonstrates the feasibility and safety of the Comaneci device as an adjunctive tool to improve vessel wall apposition during FD aneurysm embolization. This comes with the benefits of 027 catheter compatibility (no exchange) and maintenance of endoluminal flow as compared to traditional balloon technique. Disclosures: J. Campos: None. D. Zarrin: None. B. Meyer: None. K. Golshani: None. N. Beaty: 2; C; Proctor for Medtronic Neurovascular, Stryker Neurovascular, CMO of NeuroMedica. M. Bender: None. G. Colby: 2; C; Consultant for Medtronic Neurovascular, MicroVention-Terumo, Stryker Neurovascular. A. Coon: 2; C; Consultant/Proctor: Avail MedSystems, Imperative Care, InNeuroCo, Medtronic Neurovascular, MicroVention-Terumo, Q'apel, Rapid Medical, Stryker Neurovascular, Sequent Medical. L. Lin: 2; C; Consultant/Proctor: Medtronic Neurovascular, Stryker Neurovascular, MicroVention-Terumo, Rapid Medical, Bolt.